An Overview of English Dictionaries of Abbreviations - Mojca Kompara Lukančič (Lexikos, 2020)
This article addresses the position of specialized dictionaries of abbreviations for English. Special attention is given to the macro- and microstructure of English dictionaries of abbreviations, and current available online sources for users are presented. The article compares the micro- and macrostructure of seventeen English dictionaries of abbreviations, including general and language-specific ones, and three online general dictionaries of abbreviations. In the article two contemporary online attempts are also presented; namely, Slovarček krajšav (Kompara Lukančič 2006) and Slovar krajšav (Kompara Lukančič 2011). The article points out that traditional lexicography, mainly its orientation toward compiling functional and detailed entries, should be joined with modern concepts of lexicography oriented toward an extensive number of entries and constant development and improvement of a dictionary as new abbreviations are gradually added. The combination of traditional and modern concepts can develop resources that users need most — namely, a contemporary dictionary of abbreviations.